Trends of eye lid carcinoma in Chhattisgarh state of India and their outcome with high dose interstitial brachytherapy - Kerketta, Manjula; Bali Rathore, Vikram; Choudhary, Vivek; Kumar Azad, Surendra (International Journal of Medical Research and Review, 2015)
Introduction: Sight is the most precious of all senses. Tumors of the eye and orbit can be life threatening and causes blindness and disfiguring. In planning management the threat to life with disfigurement is the primary issue to be faced with, the best treatment aimed is to cure and long term control having priority. With this aim our study is to report the trend of eyelid cancer in Chhattisgarh state of India and their outcome with High Dose Rate Interstitial Brachytherapy. Material and Methods: Thirty Six Patients with histo-pathologically confirmed malignant eyelid tumours previously untreated and registered at the Department of Radiotherapy, Pt. J.N.M. Medical College and Regional Cancer Centre, Raipur, were considered in the present study. Registered patients were classified to find out general trend of occurrence in Chhattisgarh, India. Post- treatment patients were reviewed for five years to study the outcome of high dose rate interstitial brachytherapy (HDRIBRT) of eyelid cancer. Results and Discussion: Male predominance was seen in the patients of eyelid tumors. The occurrence of eyelid tumour was found higher (72.2%) in the patients with age above 60 years and 27.8% were less than 60 years old. Anatomically majority of malignancies found in upper eyelid than lower eyelid. Post Treatment follow up ranged from 10 months to 5 years in which all the patients remained locally controlled. Conclusions: Histo-pathologically SCC predominantly found in males than female. The excellent results of interstitial brachytherapy prove that it may be one of the efficient modality for the treatment of carcinoma eyelid.